If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + n + -6 = 0 Reorder the terms: -6 + 2n + n = 0 Combine like terms: 2n + n = 3n -6 + 3n = 0 Solving -6 + 3n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3n = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 3n = 0 + 6 3n = 0 + 6 Combine like terms: 0 + 6 = 6 3n = 6 Divide each side by '3'. n = 2 Simplifying n = 2
| 5n+3=23 | | 4.9X=4.4+19.1 | | 50-2x=16x+22 | | 9y^2-6y=3y | | y=-(2/3)5+30 | | 10=-(2/3)x+30 | | 4b+5b+2=0 | | y+2(y-3)=6 | | 5=-(2/3)x+30 | | 58-5x=22+22x | | -1=3+5x-3x | | x+9=5(4x+2) | | -a-a=8 | | -6x^2+8-5+3x+2x-4x^2= | | -7=n-5-5 | | 2k+4k=12 | | 36z^2+96x+15=0 | | -2x+1-6x=9 | | 16x^2-48x=-27 | | 2n=4*-8 | | -6k-6k=-12 | | 2.4x^2+5.2x+1.5x^2-0.2x= | | 1-4m-3m=-13 | | x-7=-2x-2 | | 10w-16w=54 | | 12=-2n+5n | | -9=.75m | | 2.4x^2+5.2x+1.5x^2+0.2x= | | 63-6x=3x+17 | | X(4+x)=18 | | 2(-3x+4)+4(4x-3x)=4 | | 3x-5y=-3 |